An Investigating the use of Dixon's 'sit' subtype of rest in English and Selayar Language - Husnul Khatimah Nur; Harlinah Sahib; Karmila Mokoginta (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
The study was about Investigating ‘sit’ subtype of Rest in English and Selayar language. The objectives of the research were to investigate the Rest verbs in English and Selayar language according to sit subtype based on Dixon’s theory and to identify the differences and the similarities between English and Selayar Language based on the semantic and the grammatical construction. The data about sit subtype in English was collected by using Corpus of Contemporary American English (COCA), and the data from Selayar language was collected by interviewing the people who use Selayar language and observation. The qualitative descriptive analysis was used to investigate the data. The study reveals that some rest verbs belong to the sit subtype. They exist; Kneel, crouch, squat, lean, hang down, float, and assemble are all forms of sitting. Furthermore, in the Selayar language shows some words that refers to sit subtype of rest. They are; toolong, akkedeng, doko’-doko’, toolong kabetaang, tingro-tingro, deporo’, tolong jaha, akkalantu’, A’lanto, A’bingkojeng, Ammenteng, a’se’re, a’rupa,  and assendere’. The differences between English and Selayar language that is in Selayar language some verbs using prefix a_. it can be seen in this research. There are some words that start with prefix a_. while in the sentence structure, they use the same grammatical construction between English and Selayar Language.